Introducing High School Biology Students to Argumentation About Socioscientific Issues - Dawson, Vaille; Venville, Grady (University of Toronto Press, 2013)
The purpose of this research was to determine whether teaching argumentation to high school biology students improved their argumentation skills, informal reasoning, and genetics understanding. Using a quasi-experiment with mixed methods of data collection, five teachers participated in professional learning on argumentation and socioscientific issues and then explicitly taught argumentation skills in a genetics context. Using a written survey, the experimental group of students (n = 133) improved significantly more in their argumentation skills (p < .001), ability to use rational informal reasoning (p < .001), and genetics understanding (p < .001) than the control group of students (n = 160) who studied the same genetics topic without being taught argumentation skills.